KEKUATAN HUKUM JUAL BELI TANAH MELALUI SEORANG KUASA - Rumelda Silalahi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
This study aimed at determining the legal strength of land sale and purchase through the power of an attorney. The method used in this study was sociological juridical, in which the author examined the fact based on the legislation that regulates the problem by looking directly at the implementation and application of these regulations in practice. The method of data analysis in this study was analytical descriptive wherein in this process the researcher actively and subjectively performed the process of interpreting, interpreting, and evaluating the collected data based on the theoretical framework and understanding that developed when interpreting the data. The results of the research obtained showed that the sale and purchase of land through the power of an attorney had a legal force that was legal and bound the authority and the third party concerned had to carry out the contents of the agreement. This was because the authorizer had to implement the agreement made by the recipient of the power of an attorney, as long as the recipient of the power did not exceed the authority granted to him. If there was a dispute, the party who become the party was the authorizer and the third party was not the recipient of the power of the attorney. Whereas the problems arising in connection with the sale and purchase of land through the power of an attorney in a court hearing stipulated the provisions of the Civil Code, UUPA No. 5 1960 and Government Regulation No. 10 of 1961 concerning land registration.